TRANS-PACIFIC PARTNERSHIP SEBAGAI BAGIAN DARI STRATEGIREBALANCINGAMERIKA SERIKAT DI KAWASAN ASIA PASIFIK - , SHABRINA ANNISARASYIQ; , Drs. Riza Noer Arfani, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper is explaining the role of United States involvement in the Trans- Pacific Partnership negotiation in the US strategic rebalancing toward Asia- Pacific. The ârebalancing to Asiaâ strategy is Administration Obama foreign policy strategy which prioritize Asia-Pacific region in every US foreign policy. The rebalancing itself was created due to the shift in the worldâs geo-politics and geo-economics that make Asia-Pacific region becoming more important to United States than ever before. In this strategy, Washington manage to adjust its economic, diplomatic, and security policy to enhance its engagement in the most dynamic region and the main driver of world economy. The Trans-Pacific Partnership Agreement (TPP/TPPA) is one of Obamaâs current trade policy and also part of the rebalancing strategy in Asia-Pacific. TPP is often stated as the cornerstone of US economic rebalancing in the region. The agreement that being negotiated by twelve countries in the Asia and Pacific is projected as the stepping stone of the establishment of Free Trade Area in the Asia and the Pacific (FTAAP). In this paper, the author tries to analyze the reason behind why United States considering that this negotiation is important for US rebalancing strategy. Through the liberal internationalism perspective, the author sees that as a free trade, TPP have some benefits beyond US economic interest in the Asia-Pacific region. Not only able to help the economic recovery process in the US, TPP also help United States to achieve its interest in diplomatic dimension and strategic dimension in the Asia-Pacific. Moreover, through the regionalism perspective, the author able to analyze why US now changing its approach toward Asia-Pacific by using regionalism such as TPP to engage with the region.